Palpigrades from Cuba (Arachnida: Palpigradi: Eukoeneniidae) - Mayoral, Jaime; Hernández-Borroto, Samuel (Zootaxa, 2023)
The knowledge of palpigrades in Cuba is limited to the species Eukoenenia orghidani, discovered and described from Cueva de Bellamar. In this work, a survey for palpigrades in the suburbs of La Habana, Cuba revealed three species, Eukoenenia berlesei, Eukoenenia florenciae and a new species described here as Eukoenenia glandulosa sp. nov. Interestingly, the three species coexist in the microspaces of wet soil. A total of 16 arthropod species were identified living in the same microhabitat as the palpigrades.